The impact of the live broadcast of Stromae’s song L’enfer on social media publications, calls to the national helpline, and suicide attempt rates in France - Charles-Edouard Notredame; Chloé Saint-Dizier; Antoine Lamer; Erika Nogue; Emile Fares; Mohamed Lemdani; Guillauma Vaiva; Philippe Courtet; Emilie Olié (European Psychiatry)
On January 9, 2022, Belgian pop singer Stromae performed his new hit “L’enfer” live on French TV. The song addresses his personal struggles with suicidal ideation. To evaluate the impact of Stromae’s performance, we modeled the evolution of hospital admission rates for suicide attempts (SAs) in France, calls to the national suicide prevention helpline (3114), and Twitter publications mentioning the singer or the helpline. We employed the Gombay test to identify change points within each time series. We identified a significant increase in mean SA rates among women aged 20–24 years 6 days after the singer’s performance. No similar effect was observed in the general population or other young age groups. The show was immediately followed by a peak in tweets referring to the singer, while Twitter activity related to the 3114 remained modest. We did not observe any increase in calls to the helpline. Celebrity testimonies about suicidal experiences can help alleviate stigma but should be accompanied by prevention messages to reduce the risk of contagion.